Pollen tube contents from failed fertilization contribute to seed coat initiation in Arabidopsis - Liu, Xiaoyan (F1000 Research Limited, 2019)

(untitled) (F1000Res)
Plant seeds are essential for human beings, constituting 70% of carbohydrate resources worldwide; examples include rice, wheat, and corn. In angiosperms, fertilization of the egg by a sperm cell is required for seed formation; therefore, fertilization failure results in no seed formation, except in the special case of apomixis. Initially, plants produce many pollen grains inside the anthers; once the pollen grain is deposited onto the top of the pistil, the pollen tube elongates until it reaches the ovule. Generally, only one pollen tube is inserted into the ovule; however, we previously found that if fertilization by the first pollen tube fails, a second pollen tube could rescue fertilization via the so-called fertilization recovery system (FRS). Our previous reports also demonstrated that failed fertilization results in pollen tube-dependent ovule enlargement morphology (POEM), enlarged seeds, and partial seed coat formation if the pollen tube releases the pollen tube contents into the ovule. However, we have not determined whether all the ovules enlarge or produce seed coats if an ovule accepts the pollen tube contents. Therefore, we conducted a partial seed coat formation experiment taking into account both the FRS and POEM phenomena. Notably, the ratios of failed fertilization and the ovules with partial seed coats matched, indicating that all ovules initiate seed coat formation if the fertilization fails but the pollen tube contents enter the ovule. In addition, we confirmed that the agl62 mutant , defective in early endosperm formation, showed seed coat initiation with and without fertilization, indicating that for a normal seed coat initiation, fertilization is not required; however, for the completion of normal seed coat formation, both normal fertilization and endosperm formation are required. Further molecular evidence is required to understand these phenomena because very few factors related to FRS and POEM have been identified.